Support and Interface Effects in Water‐Splitting Electrocatalysts - Zhang, Jian; Zhang, Qiuyu; Feng, Xinliang (Advanced materials (Weinheim), 2019)
Water‐splitting electrolyzers that can convert electricity into storable hydrogen are a fascinating and scalable energy conversion technology for the utilization of renewable energies. To speed up the sluggish hydrogen and oxygen evolution reactions (HER and OER), electrocatalysts are essential for reducing their kinetic energy barriers and eventually improving the energy conversion efficiency. As efficient strategies for modulating the binding ability of water‐splitting intermediates on electrocatalyst surface, the support effect and interface effect are drawing growing attention. Herein, some of the recent research progress on the support and interface effects in HER, OER, and overall water‐splitting electrocatalysts is highlighted. Specifically, the correlation between the electronic interaction of the constituent components and the electrocatalytic water‐splitting performance of electrocatalysts is profoundly discussed, with the aim of advancing the development of highly efficient water‐splitting electrocatalysts, which may eventually replace the noble‐metal‐based electrocatalysts and bring the practically widespread utilization of water‐splitting electrolyzers into a reality. Water‐splitting electrolyzers are a promising energy conversion technology for high‐efficiency hydrogen production. Key progress on the support and interface effects in water‐splitting electrocatalysts is highlighted. The correlation between the electronic interaction and the electrocatalytic activity of catalysts is emphatically discussed, with the aim of advancing the rapid exploration of high‐activity water‐splitting electrocatalysts.